Polymorphisms in DENND1B gene are associated with asthma and atopy phenotypes in Brazilian children. (October 2017) - Fiuza, Bianca S.D.; Silva, Milca de J.; Alcântara-Neves, Neuza M.; Barreto, Maurício L.; Costa, Ryan dos S.; Figueiredo, Camila A.
Highlights: Polymorphisms in the DENND1B are significantly associated with asthma and/or allergy markers. Some polymorphisms decrease DENND1B expression, lead to TCR internalization slowed down and prolonged TCR signaling. Prolonger TCR signaling leads to stronger production of effector Th2 cytokines and asthma. These SNPs may offer an impact on the occurrence of these asthma and allergy conditions in Brazilian population. Abstract: Asthma is a heterogeneous disease associated with a complex basis involving environmental factors and individual variabilities. The DENN Domain Containing 1B ( DENND1B ) gene has an important role on T cell receptor (TCR) down-regulation on Th2 cells and studies have shown that mutations or loss of this factor can be associated with increased Th2 responses and asthma. The aim of this work is to evaluate the association of polymorphisms in the DENND 1B with asthma and allergy markers phenotypes in Brazilian children. Genotyping was performed using a commercial panel from Illumina (2.5 Human Omni bead chip) in 1309 participants of SCAALA (Social Change, Asthma, Allergy in Latin American) program. Logistic regressions for asthma and atopy markers were performed using PLINK software 1.9. The analyzes were adjusted for sex, age, helminth infections and ancestry markers. The DENND 1B gene was associated with different phenotypes such as severe asthma and atopic markers (specific IgE production, skin prick test and IL-13 production). Among the 166 SNPs analyzed, 72 were associated with asthma and/or allergy markers. In conclusion, polymorphisms in the DENND 1B are significantly associated with development of asthma and atopy and these polymorphisms can influence DENND 1B expression and consequently, asthma.